MEDIA CONVERGENCE IN THE SAMUTRI ANDARU LARAS GAMELAN COMMUNITY IN PRESERVING TRADITIONAL ARTS - Yulinda Nur Fitriana; Mite Setiansah; Edi Santoso (Laboratorium Ilmu Komunikasi Fisip UHO, 2023)
The media convergence utilized by the @SALGamelan community includes Y and Z generations in distributing their gamelan music. Still, this community needs to maximize the use of digital platforms it uses, such as Instagram, TikTok, and YouTube. This study aims to analyze efforts to use digital communication media samutri andar laras in preserving traditional arts. This research method uses a post-positivism paradigm with a qualitative approach, and this type of research is descriptive; the data collection technique for this research is through interviews, documentation, and literature studies. Furthermore, the validity of the data used is source triangulation. Based on the results of this study, it was found that efforts to utilize digital music platforms are ideas for preserving traditional arts, especially gamelan music. Then create content on the social media of the SAL community. Apart from creating content, gamelan music preservation is done through mini shows at the National Museum, Jakarta, and gamelan introduction workshops are routinely held monthly at Graha Puspatarini, South Jakarta. Individual and community awareness of cultural preservation must be increased by creating content and participating in traditional music community events.community events